INVESTIGATION OF ALTERNATIVE CHEMICAL OXIDATION METHODS FOR COD DETERMINATION AVOIDING DICHROMATE AND MERCURY - , MAI ANUGRAHWATI; , Prof. Dr. Endang Tri Wahyuni, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In chemical oxygen demand (COD) determination, according to the standard methods, K2Cr2O7 is used as an oxidant and Hg is used in order to inhibit interference of Cl-. K2Cr2O7 and Hg are characterized as toxic substances. In this study, Na2S2O8 and Mn(III) were used as oxidants and in order to inhibit Cl- interference, precipitation using Ag2SO4, removal using anion exchanger and oxidation using bismuthate were investigated. As reference substances for the COD method development, potassium hydrogen phthalate (PHP), glycine, glutamic acid, L-cystein, sodium acetate, and cellulose were used. Oxidation was conducted in the open and closed reflux system followed by COD determination using spectrophotometry or titrimetry. The results showed that precipitation with Ag2SO4 and oxidation with bismuthate could basically be applied in order to inhibit up to a concentration of 1000 mg Cl-/L. Anion exchanger as an alternative method for Cl- removal and Na2S2O8 as an alternative oxidant were found to be inappropriate for the COD test. Mn(III) was found to work in principle as an alternative oxidant to K2Cr2O7. Efficiency of the oxidation for some samples using Mn(III) was comparable to DIN 38409-41. In case of glycine, Mn(III) gave 103% oxidation recovery which was better than DIN 38409- 41 (34%). Combination between oxidation using Mn (III) and Cl- elimination with bismuthate showed a better oxidation method (average recovery rates for PHP COD of 99%) than with precipitation using Ag2SO4 (average recovery rates for PHP COD of <65%).